Job dissatisfaction and its related factors among laboratory staff - Fadaei, Nehzat; Zainuddin, Huda; Syed Hassan, Syed Tajuddin (Tehran University of Medical Sciences, 2014)
Background: The purpose of this study was to determine the prevalence of job dissatisfaction, and to ascertain the association between job strain and job dissatisfaction and socio-demographic and occupational factors among laboratory staff of Universiti Putra Malaysia (UPM). Methods: This cross-sectional study was conducted among 450 research laboratory staff in 10 faculties and 8 institutes of Universiti Putra Malaysia. Probability appropriate to size sampling and simple random sampling method were used and data were collected via Job content Questionnaire (JCQ) from September 2012 to February 2013. SPSS (version 20.0) software was used for data analysis. Results: A total of 285 laboratory staff with at least one year job tenure participated in this study (Response rate: 91.3%). The finding revealed that 47% of laboratory staff reported job dissatisfaction. The results of this survey showed laboratory staffs with age 35, and less were two-fold more likely to report job dissatisfaction than the older staff (adjusted OR= 2.108, 95% CI: 1.241- 3.582). Laboratory staffs with higher toxic exposures 2 times more likely to report job dissatisfaction (adjusted OR= 1.887, 95% CI: 1.062-3.353). Conclusion: There is a need to have training plans to increase the knowledge on toxic exposures among younger laboratory staff, which may be helpful to reduce job dissatisfaction among them.